Detection and Localization of Eu on Biosilica by Analytical Scanning Electron Microscopy - Hieckmann, Ellen; Kammerlander, Kaitlin K. K.; Koehler, Lydia; Neumann, Laura; Saager, Stefan; Albanis, Nico; Hutsch, Thomas; Seifert, Frank; Brunner, Eike (Microscopy and Microanalysis, 2021)
Algae like diatoms are widely studied as a means to remediate anthropogenically contaminated sites. In the present study, CL (cathodoluminescence) and EDX (energy-dispersive X-ray) spectroscopy in an SEM (scanning electron microscope) were optimized for the detection of Eu(III) sorbed on diatom biosilica. The required stability of biosilica under a focused electron beam was extensively investigated. Using experimentally determined data of thermal properties, the temperature increase within biosilica exposed to an electron beam was simulated by finite element calculations based on results from Monte Carlo simulations of electron scattering. Complementary thermogravimetric studies substantiated a chemical stability of biosilica in a wide temperature range, confirming its suitability for long-lasting SEM investigations. In subsequent EDX measurements, characteristic Eu lines were detected. Eu was found to preferentially accumulate and aggregate on silica fragments. CL spectra were obtained for the Eu(III) reference material, EuCl3. For Eu-loaded biosilica, even parts without detectable Eu signal in the EDX spectra show significant Eu(III) signals in the CL spectra. This highlights the sensitivity of CL in studying f-element sorption. CL data showed that Eu(III) was distributed on the entire surface. In conclusion, this work demonstrates the merit of CL and EDX methods for sorption studies on biogenic materials.
CRIS-Team Scopus Importer:2022-04-14
Keywords: cathodoluminescence; diatoms; europium; Monte Carlo simulation; SEM